2017
DOI: 10.1016/j.cjca.2016.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Canadian Cardiovascular Society Guidelines on Perioperative Cardiac Risk Assessment and Management for Patients Who Undergo Noncardiac Surgery

Abstract: The Canadian Cardiovascular Society Guidelines Committee and key Canadian opinion leaders believed there was a need for up to date guidelines that used the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system of evidence assessment for patients who undergo noncardiac surgery. Strong recommendations included: 1) measuring brain natriuretic peptide (BNP) or N-terminal fragment of proBNP (NT-proBNP) before surgery to enhance perioperative cardiac risk estimation in patients who are 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
601
3
91

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 658 publications
(705 citation statements)
references
References 94 publications
10
601
3
91
Order By: Relevance
“…International guidelines promote the utility of troponin surveillance, and a recent study found troponin surveillance to be financially viable in SA. [39,40] Our data suggest that postoperative troponin surveillance is necessary in elevated-risk non-cardiac surgical patients in SA.…”
Section: Resultsmentioning
confidence: 99%
“…International guidelines promote the utility of troponin surveillance, and a recent study found troponin surveillance to be financially viable in SA. [39,40] Our data suggest that postoperative troponin surveillance is necessary in elevated-risk non-cardiac surgical patients in SA.…”
Section: Resultsmentioning
confidence: 99%
“…It also warns that the tolerated beta-blocker dose before surgery is not necessarily safe because hypotension is common during or after surgery (6). The guideline has no specific recommendation about titration.…”
Section: Titration and Durationmentioning
confidence: 99%
“…Based on this systematic review, the 2017 CCS guideline recommends against the initiation of betablockers in the last 24 hours before surgery. The guideline has no specific recommendation about when to start the drug (6).…”
Section: Time Of Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Moreover, in the VISION study, patients with MINS who died did so a mean of 9 days after their initial troponin T level elevation, which indicates that there is time to initiate treatment after MINS is detected. Perhaps as a consequence, Canadian 5 and international 6 guidelines recommend troponin monitoring after noncardiac surgery in patients at high cardiovascular risk.…”
mentioning
confidence: 99%